Under Glass Weathering of Hemp Fibers Reinforced Polypropylene Biocomposites: Degradation Mechanisms Based on Emitted Volatile Organic Compounds - Badji, Célia; Sotiropoulos, Jean-Marc; Beigbeder, Joana; Garay, Hélène; Bergeret, Anne; Bénézet, Jean-Charles; Desauziers, Valérie (Frontiers in Materials, 2020)
Natural fibers composites are more and more integrated in different car parts including dashboards. These pieces can be source of odor and/or volatile harmful substances. In this work, the durability of hemp fibers reinforced polypropylene biocomposites was investigated after one-year under glass exposure to simulate car interior environment. Volatile Organic Compounds (VOCs) emissions were assessed using a new passive sampling method all along the weathering. The objective of this paper was to understand the degradation pathways and thus, the weathering mechanisms thanks to the emitted VOCs identification. The polymer matrix was decomposed into long-chain aliphatic hydrocarbons and oxygenated products due to UV rays and high temperatures. As regards hemp fibers, different degradation steps of the carbohydrates were highlighted according to the nature of the detected furans. At non-weathered state, dehydrations preceded ring-opening mechanism, often catalysed by Maillard reactions. The further cyclisation induced the formation of 2- or 5-substituted furans emitted by non-weathered materials. Reactions between identified products after weathering which were not yet found in literature were proposed in this paper. They often implied a keto-enol tautomerism but also dehydrations that induced the formation of 3- and 4-substituted furanones. These differences can be explained by a primary decomposition of carbohydrates favoured at non-weathered state and a secondary one occurring at weathered state. As regards lignin decomposition, methoxyphenols, detected at non-weathered state, were explained by hydration and oxidation whereas dimethylphenol, evolved from weathered biocomposites, could originate from radical reactions.